ANALYSIS OF TASKS AND TESTS IN MATHEMATICS FOR EIGHTH GRADE IN NINE-YEARS PRIMARY SCHOOL - Saliji, Mejdin; Velkoska, Aneta; Dimovski, Dončo (Matematichki Bilten, 2016)
The objective of teaching mathematics is active and creative proficiency of knowledge that will be durable and applicable in practice. Therefore, it is necessary to have competent teachers. A very important segment of the teachers’ education is their ability for preparing and evaluating the tests of knowledge which satisfy all measuring characteristics and make the test a measuring instrument of the students’ knowledge. In this paper we examine to what extent the teachers at mathematics in primary schools could prepare achievement tests with all measuring characteristics. Moreover, in this paper by performing thorough test and items analysis we prepare a final achievement test in mathematics in the eighth grade from nine-year primary schools.